Communique Issued at the End of the First International Conference on Community, Trade and Religion in Coastal Yorubaland and Western Niger Delta, Held at Adeyemi College of Education, Ondo, from 6–8 December 2016 - Yoruba Studies Review (Yoruba Studies Review)
An international conference was held from December 6 to 8 2016 at Adeyemi College of Education Ondo, with the theme “Mobile Populations, Fluid Boundaries: Community, Trade and Religion in Coastal Yorubaland and the Western Niger Delta.” The conference was sponsored by the European Research Council (ERC), and jointly organized by the University of Birmingham, Osun State University, and Adeyemi College of Education.